Effects of long-term fertilization on soil organic carbon content and aggregate composition under continuous maize cropping in Northeast China. (March 2015) - SONG, Z. W.; ZHU, P.; GAO, H. J.; PENG, C.; DENG, A. X.; ZHENG, C. Y.; MANNAF, M. A.; ISLAM, M. N.; ZHANG, W. J.
SUMMARY Fertilizer application can play an important role in soil organic carbon (SOC) retention and dynamics. The mechanisms underlying long-term accumulation and protection of SOC in intensive maize cropping systems, however, have not been well documented for cool high-latitude rainfed areas. Based on a 23-year fertilization experiment under a continuous maize cropping system at Gongzhuling, Jilin Province, China, the effects of fertilization regimes on SOC content and soil aggregate-associated carbon (C) composition were investigated. Results showed that, within the 0–1·0 m soil profile, SOC contents decreased significantly with soil depth in all treatments. In the topsoil layer (0–0·2 m), SOC concentrations in balanced inorganic fertilizers plus farmyard manure (MNPK), fallow system (FAL) and balanced inorganic fertilizers plus maize straw residue (SNPK) treatments were significantly greater than initial levels by 61·0, 34·1 and 20·1%, respectively. The MNPK and SNPK treatments increased SOC content by 50·7 and 12·4% compared to the unfertilized control in the topsoil layer, whereas no significant differences were found between balanced inorganic nitrogen, phosphorus and potassium fertilizers (NPK) and the unfertilized control treatment. There were no significant differences in aggregate-size distribution among the unfertilized control, NPK and MNPK treatments, whereas the SNPK treatment significantly enhanced the formation of micro-aggregates (53–250 μm) and decreased the formation of silt+clay aggregates (<53 μm) compared to the unfertilized control, NPK and MNPK treatments. Moreover, SOC concentrations in all aggregate fractions in the MNPK treatment were the highest among treatments. Furthermore, the MNPK treatment significantly increased SOC stock in micro- and silt+clay aggregates, which may slow down C decomposition in the soil. These results indicate that long-term manure amendment can benefit SOC sequestration and stability in the black soil of Northeast China.